So close and yet so far away: A psychological distance account of the effectiveness of leader appeals. Issue 12 (5th October 2017) - van Houwelingen, Gijs; Stam, Daan; Giessner, Steffen
Abstract: Contradictory recommendations persist on how leaders best communicate goals to followers. Whereas scholars of visionary leadership recommend emphasizing the desirability of preferred end‐states, scholars of goal setting argue that the perceived feasibility of a goal determines motivation. This paper proposes and tests a synthesis based on construal level theory. Under relatively high (i.e., abstract) levels of construal, such as when leader–follower distance is relatively large, leader appeals that emphasize desirability (i.e., desirable appeals) are more likely to be effective than appeals that emphasize feasibility (i.e., feasible appeals). Under relatively low (i.e., concrete) levels of construal, such as when leader–follower distance is relatively small, feasible appeals are more likely to be effective. Two experimental studies in two different countries provide support for our predictions.